2019
DOI: 10.1681/asn.2019050538
|View full text |Cite
|
Sign up to set email alerts
|

Detection of PLA2R Autoantibodies before the Diagnosis of Membranous Nephropathy

Abstract: BackgroundCirculating serum autoantibodies against the M-type phospholipase A2 receptor (PLA2R-AB) are a key biomarker in the diagnosis and monitoring of primary membranous nephropathy (MN). However, little is known about the appearance and trajectory of PLA2R-AB before the clinical diagnosis of MN.MethodsUsing the Department of Defense Serum Repository, we analyzed PLA2R-AB in multiple, 1054 longitudinal serum samples collected before diagnosis of MN from 134 individuals with primary MN, 35 individuals with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
61
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 41 publications
4
61
0
2
Order By: Relevance
“…The clinical sensitivity of the ChLIA exceeded that of ELISA and RC-IFA by 10.4% and 0.7%, respectively, at similar specificities (>99%). The anti-PLA2R-positive rates detected by ChLIA (83.9%), ELISA (73.5%), and RC-IFA (83.2%) were equal to or higher than the prevalence data determined among non-preselected patients with pMN by different methods, such as Western blot (53.0%-81.7%), 10,11 RC-IFA (48.0-82.3%), 12,13 ELISA (50.0-71.8%), 14,15 addressable laser bead immunoassay (51.5-66.9%), 16,17 luciferase immunoprecipitation systems assay (53.3%), 18 and time-resolved fluoroimmunoassay (71.0-89.7%). 19,20 These variations may be due to differences in assay techniques (e.g., epitope exposure, cutoff values, detected Ig subclass) and cohort characteristics (e.g., ethnicity, immunosuppressive treatment).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The clinical sensitivity of the ChLIA exceeded that of ELISA and RC-IFA by 10.4% and 0.7%, respectively, at similar specificities (>99%). The anti-PLA2R-positive rates detected by ChLIA (83.9%), ELISA (73.5%), and RC-IFA (83.2%) were equal to or higher than the prevalence data determined among non-preselected patients with pMN by different methods, such as Western blot (53.0%-81.7%), 10,11 RC-IFA (48.0-82.3%), 12,13 ELISA (50.0-71.8%), 14,15 addressable laser bead immunoassay (51.5-66.9%), 16,17 luciferase immunoprecipitation systems assay (53.3%), 18 and time-resolved fluoroimmunoassay (71.0-89.7%). 19,20 These variations may be due to differences in assay techniques (e.g., epitope exposure, cutoff values, detected Ig subclass) and cohort characteristics (e.g., ethnicity, immunosuppressive treatment).…”
Section: Discussionmentioning
confidence: 66%
“…19,20 These variations may be due to differences in assay techniques (e.g., epitope exposure, cutoff values, detected Ig subclass) and cohort characteristics (e.g., ethnicity, immunosuppressive treatment). Recently, Burbelo et al 18 reported a quantitative PLA2R-NanoLuc luciferase immunoprecipitation system assay that provides high diagnostic performance (receiver operating characteristics area under the curve ¼ 1.0) and is, just like the novel ChLIA, more sensitive in detecting anti-PLA2R seropositivity than the ELISA. In the respective pMN panels, luciferase immunoprecipitation system found 1 and ChLIA found 16 additional anti-PLA2Rpositive samples compared with ELISA.…”
Section: Discussionmentioning
confidence: 99%
“…. ) might then induce intramolecular epitope spreading in PLA2R1 toward the C-terminal end (CTLD1, CTLD7 and/or CTLD8 domains) leading to more active disease, which may happen even before the clinical onset of MN (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…These findings led us to hypothesize that PLA2R1-Ab may be initially raised against the N-terminal CysR domain with pauci-symptomatic iMN disease: patients in the CysR group are younger, probably at the beginning of the disease. A second immune challenge (allergy, infection …) might then induce intramolecular epitope spreading in PLA2R1 toward the C-terminal end (CTLD1, CTLD7 and/or CTLD8 domains) leading to more active disease, which may happen even before the clinical onset of MN ( 35 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…11 Metabolomics might be a valid method for elucidating the pathogenic mechanisms of PLA2R-associated MN, as this condition shows highly variable clinical manifestations, despite the definite pathogenic role of anti-PLA2R autoantibody. 12,13 In the present study, we aimed to characterize the urinary metabolomic profiles of PLA2Rassociated MN, assess the prognostic value of metabolites that could reflect disease activity, and investigate the role of these metabolites in podocyte biology via in vitro experiments mimicking the PLA2R-associated MN milieu.…”
Section: Introductionmentioning
confidence: 99%